2018
DOI: 10.1055/s-0038-1636908
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intravenous Acetaminophen on Lengths of Stay and Discharge Status after Total Knee Arthroplasty

Abstract: Postoperative pain remains difficult to control after total knee arthroplasty (TKA). While various modalities have been used, they have been associated with several side effects. For example, opioids have many side effects including: sedation, dizziness, nausea, vomiting, constipation, respiratory depression, and can lead to dependency. Recently, intravenous (IV) acetaminophen has been introduced as a method to manage postoperative pain. Therefore, the purpose of this study was to compare the postoperative out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…This protocol takes advantage of multiple medications, including nonsteroidal anti-inflammatory drugs (NSAIDs), selective cyclooxygenase-2 (COX-2) inhibitors, acetaminophen, and glucocorticoids, that exert their mechanisms of action on different targets of the pain pathway. Intraoperative intravenous acetaminophen and a periarticular cocktail injection containing liposomal bupivacaine have been demonstrated to result in a reduced need for postoperative opioids and fewer postoperative complications after TJA [19][20][21][22][23][24][25][26][27][28][29]. Postoperatively and on discharge, a standing dose of 1 g of oral acetaminophen every 6-8 hours was used for preemptive analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…This protocol takes advantage of multiple medications, including nonsteroidal anti-inflammatory drugs (NSAIDs), selective cyclooxygenase-2 (COX-2) inhibitors, acetaminophen, and glucocorticoids, that exert their mechanisms of action on different targets of the pain pathway. Intraoperative intravenous acetaminophen and a periarticular cocktail injection containing liposomal bupivacaine have been demonstrated to result in a reduced need for postoperative opioids and fewer postoperative complications after TJA [19][20][21][22][23][24][25][26][27][28][29]. Postoperatively and on discharge, a standing dose of 1 g of oral acetaminophen every 6-8 hours was used for preemptive analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Barrington et al also performed a retrospective review of the Premier database and evaluated the postoperative outcomes of patients who received IV versus oral acetaminophen after undergoing total knee arthroplasty. 15 This study demonstrated that when compared with the oral group, patients who received IV acetaminophen had a shorter length of stay (0.14 days, P < .001), 13% lower chance of discharge to a skilled nursing facility (P < .001), and a 22% higher likelihood of being discharged to home (P < .001). Apfel et al also performed a retrospective matched-pairs analysis of the Premier database, evaluating patients who underwent total hip or total knee arthroplasty with each patient who received IV acetaminophen on the day of surgery being matched to a patient who did not receive IV acetaminophen during that hospitalization.…”
Section: Discussionmentioning
confidence: 74%
“…However, the higher cost of individual IV APAP dose was not included in the cost calculation, and may decrease the overall savings. Another study is underway comparing LOS and discharge disposition between those who received IV and PO APAP 45 Prospective randomized controlled studies are needed to verify these results. Future studies should assess costs, LOS, and discharge status in patients who use IV APAP.…”
Section: Resultsmentioning
confidence: 99%